Performance Evaluation of Nonlinear PI Controller on the Laboratory Type Spherical Tank Process - Bhuvanendhiran, T.; Lincon, S. Abraham (Asian Journal of Electrical Sciences, 2019)
In this paper, the implementation of Nonlinear PI controller based on error square type is designed and adopted to control of level in a spherical tank process. By use of black box model the system is found as a First order plus Dead Time model (FOPDT). Then the controller tuning strategies has been adopted namely Direct synthesis (IMC), Skogestad (IMC PI), and Nonlinear PI (error square type) tuning. Among all the three controllers tuning the error square type based Nonlinear PI tuning method shows better control performance than the other two controller tuning in terms of performance indices like Integral Square Error (ISE), Integral Absolute Error (IAE) and Time domain specifications